KELUARGA DALAM KAJIAN SOSIOLOGI - Rustina Rustina (Musawa: Journal for Gender Studies, 2022)
Analysis of the role of the family in society is sometimes not realized and neglected. The position of parents seems to only be in charge of providing physical services. However, it is very rare to deal with the religious, moral, ethical education of the child. If parents cannot give their children their maximum role, of course the child's attitude tends to make justifications for even the wrong things. Because, it is to parents that children identify themselves. The process of imitating the normative values of parents in their daily lives becomes a certainty so that it is not wrong if there is an idiom the child is a reflection of the parents. We are not surprised that many students who graduate have very high formal and scientific educational values. However, the moral character of his personality is still questionable. In other words, character education in schools is only capable of producing 'pragmatic' people, not 'intellectual' moral qualities.